Pengaruh Pelayanan (FL) dan SIA terhadap Minat Penggunaan Wallet Digital Studi Kasus pada Mahasiswa Akuntansi Politeknik Negeri Lampung - Niska Kurnia Victoria; Endah Yuni Puspitasari; Arif Makhsun (Journal of New Trends in Sciences, 2025)
This research aimed to examine the influence of service quality and System Information Assurance (SIA) on the interest in using digital wallets among Accounting students at Politeknik Negeri Lampung. A purposive sampling method was employed, with a sample of 102 respondents selected through the distribution of questionnaires to Accounting students at the institution. The study focused on understanding how service quality and the assurance of system information (SIA) impacted the adoption and usage of digital wallets, which are increasingly popular in modern financial transactions. The data was analyzed using IBM SPSS version 26, employing statistical tests to determine the strength and significance of the relationship between these variables. The results of the analysis indicate that both service quality and SIA significantly influence students’ interest in using digital wallets. Specifically, the study found that better service quality and higher assurance of system security contribute positively to the students’ trust and interest in utilizing digital wallet applications. These findings suggest that financial service providers should prioritize improving service quality and strengthening system security measures to attract younger users, especially in academic settings where digital wallet usage is becoming more prevalent. Additionally, this research emphasizes the importance of understanding the factors that drive digital wallet adoption, particularly in the context of higher education students, who are key early adopters of digital payment solutions. The study’s findings offer valuable insights for digital wallet providers, educators, and policymakers in shaping strategies to enhance the acceptance and use of digital wallets among students in academic environments.